AIP Conference Proceedings Book WSCC 2021 - Putra Jaya, Ramadhansyah (AIP Publishing, 2023)
This volume of conference proceeding not only has a good selection of refereed papers but there are more to it. You will find a compilation of 4 keynote lectures given by Professor Dr. Yukio Tamura, a prominent professor at the Chongqing University, China, Professor Dr. Shuyang Cao from Tongji University, China, Professor Dr. Guoqing Jing from the Beijing Jiaotong University and finally Dr. Ichwana Ramli, from Universitas Syiah Kuala, Indonesia. Many of the keynote topics discussed here was highly relevant and triggered healthy discussions and sharing of knowledge among participants. The World Sustainable Construction Conference (WSCC) also served as a new platform to researchers and scholars from different disciplines that have interest in sustainable construction, advanced materials, agricultural technology and environmental sciences to share and discuss their research findings.